Kualitas Tanah Lahan Persawahan Berdasarkan Parameter Sifat Kimia Tanah - desti liani (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
Rice fields are man-made soil whose properties are highly influenced by the way it is made and processed. This research was conducted to determine the chemical properties of the soil in various rice fields in Indonesia. The writing of this article is done by analyzing various kinds of related literature obtained from search results on the Google Scholar database. A total of 10 articles are included in this literature study with the data collected focusing on the chemical properties of the soil, namely pH, KTK and C-organic only. With Soil pH: < 4.5 or > 8.5, Soil KTK: Low, < 18 cmol/kg, Medium, ranging from 18 – 25 cmol/kg, Height, > 25 cmol/kg, C – Organic Content: Low, < 2.0 g/100g, Medium, range from 2.0-3.0 g/100g, Height, > 3.0 g/100g Based on the analysis that has been done on 10 journals, it was concluded that there is a significant correlation between pH and high and low content of KTK and C-organic. The amount of KTK is largely determined by soil pH, soil texture and C-organic content.